2022
DOI: 10.1097/yic.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of switching from benzodiazepine to orexin receptor antagonists improves cognitive function in psychiatric disorders: four case reports

Abstract: Benzodiazepines are used in the treatmentof anxiety and insomnia. On the other hand, they not only have side effects such as drowsiness, poor concentration, and muscle relaxation but also persistent cognitive decline. Even if we try to reduce the dose of these drugs to improve drug-induced cognitive function, it is difficult to do so due to dependence and worsening insomnia. I report four cases in which cognitive dysfunction was improved by switching from benzodiazepines to orexin receptor antagonists (suvorex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Orexins A and B act via G-protein type 1 and type 2 coupled receptors (OxR1 and OxR2, respectively). Orexins are known to contribute to cognitive function [ 2 ] and the stress response [ 3 ]. A reduction in orexin system function in animal models of depression was observed in a model of endogenous depression in Wistar-Kyoto rats [ 4 ] and in a model of social stress [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Orexins A and B act via G-protein type 1 and type 2 coupled receptors (OxR1 and OxR2, respectively). Orexins are known to contribute to cognitive function [ 2 ] and the stress response [ 3 ]. A reduction in orexin system function in animal models of depression was observed in a model of endogenous depression in Wistar-Kyoto rats [ 4 ] and in a model of social stress [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dual orexin receptor antagonists (DORAs), which have a mechanism of action that is not mediated by GABA receptors, were developed to address this issue. One study indicated that cognitive improvement was achieved after switching from benzodiazepine to DORAs 1 …”
Section: Introductionmentioning
confidence: 99%
“…One study indicated that cognitive improvement was achieved after switching from benzodiazepine to DORAs. 1 …”
Section: Introductionmentioning
confidence: 99%
“…In this journal, we recently reported and discussed the potential benefit of the newly available orexin receptor antagonists for insomnia (Albadrani et al ., 2023; Serretti, 2023). In this issue, a case report from Hori underlines the benefit of cognitive function after switching from benzodiazepines to the orexin receptor antagonists suvorexant and lemborexant (Hori, 2022). The results were interesting also because in two cases the benefit was observed when switching from eszopiclone, a Z-drug, which is known for a reduced potential impact on cognitive performance compared to benzodiazepines.…”
mentioning
confidence: 99%